Analysis of the atmospheric mixed layer over the western Pacific warm pool - Dickey, Jennifer A., author (Colorado State University. Libraries, 1996)
Knowledge of the atmospheric mixed layer is fundamental to understanding the ocean-atmosphere coupling over the western Pacific warm pool. In this study, we use rawinsonde data from the Tropical Ocean Global Atmosphere (TOGA) Coupled Ocean Atmosphere Response Experiment (COARE) to determine the depth of the atmospheric mixed layer over the warm pool region. Mixed layer properties (depth, potential temperature, and specific humidity) are investigated for four sounding sites: Kapingamarangi, Shyian 3, Xiangyanghong 5, and the Moana Wave. Time series from the four-month Intensive Observation Period (IOP) illustrate the long-term variability of the mixed layer. Frequent convection during COARE substantially modified the atmospheric boundary layer over a wide range of time scales (hours to weeks). These time series show that periods of strong surface winds and precipitation tend to correspond to shallow mixed layers, emphasizing the impact of convection. To investigate the mixed layer during relatively undisturbed periods we studied various light-wind cases. Histograms of mixed layer depth for light-wind periods show a more normal (Gaussian) distribution than those that include precipitation events. The mixed layer is deeper during both light-wind periods and the westerly wind bursts (after precipitation has ended). The mean mixed layer depth at the four stations analyzed ranged from 470 m to 540 m. These values are consistent with the mean mixed layer depth over other regions of the tropics, despite the larger average surface fluxes over the warm pool. For example, Fitzjarrald and Garstang (1981) found the mean mixed layer depth in the Atlantic to be 424 m while Bond (1992) concluded that it was approximately 500 m in the eastern equatorial Pacific. The possibility of a diurnal variation in the atmospheric boundary layer directly above the ocean has typically been discounted due to the relatively small variation in the tropical sea surface temperatures (SSTs). However, a perceptible variation in the boundary layer over the equatorial western Pacific is evident using TOGA COARE sounding data. The mixed layer depth over Kapingamarangi exhibited a diurnal cycle that was maximized under clear skies and light-wind conditions with the depth varying approximately 16.5% throughout the day. Potential temperature and specific humidity within the mixed layer also demonstrated diurnal cycles (with amplitudes of approximately 0.7°K and 0.4g/kg respectively). Similar diurnal variations in the mixed layer depth were found at other sounding stations in the Intensive Flux Array (IFA). The depth varied 7.6% at the Moana Wave, and 13.0% at both Shyian 3, and Xiangyanghong 5. The slightly larger variation in the mixed layer depth at Kapingamarangi may be due to a small land effect from the atoll. This study has provided a better understanding of the atmospheric mixed layer over the western Pacific warm pool. The behavior of the atmospheric mixed layer is an essential factor in the coupling between the atmosphere and the ocean. An understanding of this coupling is instrumental in improving the boundary layer parameterizations and global climate modeling.
Summer 1996.
Also issued as author's thesis (M.S.) -- Colorado State University, 1996.
Keywords: Ocean-atmosphere interaction; Boundary layer (Meteorology)